2008
DOI: 10.1037/0033-2909.134.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Hot flashes and panic attacks: A comparison of symptomatology, neurobiology, treatment, and a role for cognition.

Abstract: Despite decades of research, the causal mechanisms of hot flashes are not adequately understood, and a biopsychosocial perspective on hot flashes remains underdeveloped. This article explores overlooked parallels between hot flashes and panic attacks within 5 areas: course and symptomatology, physiological indicators, neurocircuitry and biochemical mechanisms, pharmacotherapy, and psychological treatment, noting both similarities and important differences between the 2 events. An integrative conceptual model i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 294 publications
(399 reference statements)
0
28
0
1
Order By: Relevance
“…The hypothesized shared neurocircuit model in PA and hot flashes involves several regions such as the hypothalamus, brainstem, insula, and cingulate cortex. 3 The present results suggest that there is dysregulation of these regions in PD patients with putative genetic factors. Further study is needed to confirm the identification of PA symptoms in the multiplex PD family.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…The hypothesized shared neurocircuit model in PA and hot flashes involves several regions such as the hypothalamus, brainstem, insula, and cingulate cortex. 3 The present results suggest that there is dysregulation of these regions in PD patients with putative genetic factors. Further study is needed to confirm the identification of PA symptoms in the multiplex PD family.…”
mentioning
confidence: 60%
“…2 Studies investigating candidate genes related to serotonin regulation, however, such as serotonin transporter gene, have not found any associations in PDD 3 or OCD. 4 Whether obsessive-compulsive symptoms in OCD and PDD have overlapping etiologies remain unclear.…”
mentioning
confidence: 99%
“…The reasons for relations between depressive symptoms and hot flashes are likely numerous. Depressive symptoms may predispose a woman to reporting hot flashes via changes in central neuroendocrine function (20), an elevated propensity to report physical symptoms (21), and/or in this case, sleep disturbance that may increase the likelihood of endorsing sleep-disturbing hot flashes (22). Hanisch et al similarly found elevated negative affect (anxious symptoms, typically highly correlated with depressive symptoms) to be one of the few predictors of pregnancy-related hot flashes (8).…”
Section: Discussionmentioning
confidence: 99%
“…Terápiánk sikerét leginkább az segítette elő, hogy a menopausalis hőhullámok és a szorongásos reakciók testi tünetei között felfigyeltünk a lehetséges átfedésekre [16]. Míg a hőhullámok a szexuálszteroid-szintek ingadozásával esnek egybe, addig -ha egy személy zavarba jön -adrenalinfelszabadulás következik be [11].…”
Section: Megbeszélésunclassified